The Role of Middleware in Integrating Legacy Systems with Modern Policy Administration - Padmaja Dhanekulla, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This comprehensive article examines the critical role of middleware integration in modernizing insurance industry legacy systems. The article reveals that approximately 75% of insurers rely on systems that are 20-40 years old, consuming up to 70% of IT budgets in maintenance. Through a detailed examination of implementation strategies, benefits, and challenges, the research demonstrates how middleware solutions serve as a crucial bridge between legacy infrastructure and modern Policy Administration Systems (PAS). The article covers key aspects, including protocol translation capabilities, service orchestration frameworks, and data transformation excellence, while providing quantitative metrics on cost reduction (20-30%), operational efficiency improvements (40-50%), and system performance enhancements (99.9% reliability). The article also presents a structured framework for implementing best practices, incorporating assessment, architecture design, security considerations, and testing strategies validated through industry case studies and expert analysis.
Keywords: Legacy System Modernization; Insurance Middleware Integration; Digital Transformation; Policy Administration Systems; System Implementation Metrics